The Effect of Arabica Coffee Fruit Skin Extract (Coffea arabica L.) on the Histopathology of Mice (Mus musculus L.) Liver Induced by Ethanol - Cahyani, Dini; Maliza, Rita; Setiawan, Haris (Universitas Ahmad Dahlan, 2021)
Excessive alcohol consumption can lead to serious live injury. Alcohol is a source of free radicals that can cause oxidative stress. The provision of antioxidants can counter the effects of free radicals that enter the body. The skin of the Arabica coffee fruit contains antioxidant compounds that can be used as a hepatoprotective in the liver. The skin of the Arabica coffe fruit contains antioxidant compounds that may have a hepatoprotective effect on the liver. This study aimed to determine the effect of extract of arabica coffee fruit skin on necrosis, infiltration and haemorrhage in the liver tissue of 15% EtOH-induced mice for 15 days. The animals used for this study were eight weeks old male Balb/c strain mouse weighing approximately 30-40 grams. This research is an experimental study. There were five groups: the control group (K), the 15% ethanol treatment group (E), and the ethanol-induced group and given different doses of arabica coffee skin extract: 125 mg/kg BW. (A), 250 mg / kg BW (B) and 500 mg / kg BW (C). Observation and identification of necrosis, hepatocyte infiltration and haemorrhage were carried out by using Hematoxylin-eosin staining. The data analysis used was One way ANOVA and continued by Duncan Multiple Range Test (DMRT). The histopathological observations showed that the extract of arabica coffee fruit skin at a 250 mg/kg BW dose reduced the number of cell necrosis. There was no infiltration of inflammatory and hemorrhagic cells in the liver of 15% EtOH-induced mice. This study concludes that the extract of the skin of the Arabica coffee fruit has hepatoprotective potential in 15% EtOH-induced mice.